PENGELOLAAN DANA RETRIBUSI PASAR PERSPEKTIF HUKUM EKONOMI SYARIAH (Program Studi Muamalah Fakultas Syariah dan Hukum, 2022)
This thesis is entitled about Islamic Economic Law Review of Market Levy Fund Management (Study at the Technical Implementation Unit of Pasar Bukit Sulap, Lubuklinggau City). Where is the first formulation of the problem in this thesis, how to manage market retribution funds in the technical Implementation Unit of the Lubuklinggau City marketplace Office. Second, how is the review of sharia economic law on the management of market retribution funds in the Technical Implementation Unit of the market for the Magic Hill market in Lubuklinggau City. This research was conducted based on the Local Regulation of the City of Lubuklinggau no. 14/2020 concerning market service charges. The collection of levies is carried out to finance the existence of the market such as development costs, maintenance costs, operational costs, cleaning costs, and other market service costs, it is necessary to determine the fee collection fees that have been determined by the Lubuklinggau City Government. This research method uses a type of field research (Filed Research) and the method used is a qualitative descriptive method the describes all the problems that exist in the form of words or sentences in a firm and clear manner. The data collected in this study were interviews, documentation and literature studies, primary data from this thesis were obtained through interviews. Secondary data obtained by literature study such as books, journals, articles, newspapers. This data in then analyzed by matching the data obtained with the facts or facts that occur in the field. The results of the study concluded that the market management implemented by the Technical Implementation Unit of the Lubuklinggau City Market Office Was in accordance with government regulations and was also based on Islamic economic law or syara’ Islam. Where the results obtained by the researchers in the field are that the government has provided market facilities in the form of market buildings and other market facilities that have been used by traders to sell and transact in market economic activities. The cleanliness levies collected by market managers do not impose a burden on traders while the collection is not painful for traders to pay and there is evidence of payment of market cleanliness levies in the form of a ticket given to traders for each collection. However, there are also traders who are less enthusiastic about paying the levy because sometimes the income is earned in small markets, and the review of sharia economic law on market management at the Pressis Implementation Unit, the Pasar Bukit Sulap Office, Lubuklinggau City, is legal as long as it is not against Islamic law. Keywords: Local Regulations, Management Of Market Retribution Fund, Islamic Economic Law.